On the Shannon Cipher System with Correlated - Margaryan, Tigran (Mathematical Problems of Computer Science, 2021)
In this paper the Shannon cipher system with discrete memoryless correlated sources is considered. The wiretapper gains the noisy version of the cryptogram through the memoryless noisy channel and tries to guess the secret information which is related to the encrypted plaintext. The security level of the encryption system is measured by the expected number of wiretapper's guesses. The upper and lower bounds are obtained for the guessing rate.